"Self-ie" : a study on the presentation of one's self-identity and social interaction through Instagram - Wong, Genevieve Si-Min (2015)
As one of the trendiest social media site, Instagram is a highly interactive platform that has introduced new ways of connecting and interpreting mediated messages, by using imagery as it’s main communicative medium. Focused on Instagram as a networking site, this research paper investigates how the app has introduced photographic agency through the ways in which images are taken and manipulated. Discussions from the interviews have shed light on how users utilize impression management in the creation and performance of their identities for recognition. The creation of personal photographic narratives are knowingly shared with an imagined audience in mind, where users take deliberate actions in portraying how they wish to be seen or acknowledged by others.